Towards an integrative understanding of social behavior: new models and new opportunities - Blumstein, Daniel T.; Ebensperger, Luis; Hayes, Loren; Vásquez, Rodrigo A.; Ahern, Todd H.; Burger, Joseph R.; Dolezal, Adam G.; Dosmann, Andy; Mariscal, Gabriela G.; Harris, Breanna N.; Herrera, Emilio A.; Lacey, Eileen A.; et al. (Frontiers in Behavioral Neuroscience, 2010)
Social interactions among conspecifics are a fundamental and adaptively significant component of the biology of numerous species. Such interactions give rise to group living as well as many of the complex forms of cooperation and conflict that occur within animal groups. Although previous conceptual models have focused on the ecological causes and fitness consequences of variation in social interactions, recent developments in endocrinology, neuroscience, and molecular genetics offer exciting opportunities to develop more integrated research programs that will facilitate new insights into the physiological causes and consequences of social variation. Here, we propose an integrative framework of social behavior that emphasizes relationships between ultimate-level function and proximate-level mechanism, thereby providing a foundation for exploring the full diversity of factors that underlie variation in social interactions, and ultimately sociality. In addition to identifying new model systems for the study of human psychopathologies, this framework provides a mechanistic basis for predicting how social behavior will change in response to environmental variation. We argue that the study of non-model organisms is essential for implementing this integrative model of social behavior because such species can be studied simultaneously in the lab and field, thereby allowing integration of rigorously controlled experimental manipulations with detailed observations of the ecological contexts in which interactions among conspecifics occur.